Factors associated with academic performance in psychology students of UNMSM - García Ampudia, Lupe (2002)
In the present job is studied the factors related to the academic performance in to university group of students of the Faculty of Psychology of the UN MSM, among the factors has been considered the motivation, the strategies of learning and the self-esteem and in it pertaining to the academic performance the average of notices there is been considered obtained by the students in the three first cycles of study. The sample studied was constituted by the ingresantes in the year 1,999 to the Faculty of Psychology, the instruments utilized were: the Learning Strategies Questionnaire and Motivation adapted the Spaniard by C. GRAZE, J. TOURON AND M. Gonzales, and the inventory of Selfesteem of Rosenberg, for the academic performance following Graze, Touron and Gonzales (1995) was considered three levels of performance: high, medium and under, considering the percentiles ace point of cut.